ANALISIS NILAI MORAL DAN KATA-KATA INSPIRASI DALAM NOVEL “ORANG CACAT DILARANG SEKOLAH” KARYA WIWID PRASETYO - Fiktoria Hartini Banung; Kusmiyati Kusmiyati; Tio Yoga Casenda (Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to describe: (1) The moral values ​​contained in the novel People with Disabilities Forbidden Schools by wiwid prasetyo. (2) Inspirational words contained in the novel Orang Disabled for Schools by wiwid prasetyo. In conducting this research the method I use is descriptive qualitative method. The main data source in this study comes from the novel Orang Cacat Disarang Sekolah by Wiwid Prasetyo. Data collection in this study uses library techniques with steps. Read and understand novels. Mark a quote. Invest. Clarifying Data. And finally the validity of the data is obtained through triangulation. Data analysis techniques use flow analysis techniques which include data reduction, data presentation, and drawing conclusions. Based on research conducted, it was concluded that this novel depicts an optimistic attitude in living the life of a disabled child with a strong foundation of belief in religion and God's destiny. Strong belief in religion makes the characters in the novel struggle hard to achieve their goals, even though they have physical limitations.